2014
DOI: 10.2466/08.11.pr0.114k16w1
|View full text |Cite
|
Sign up to set email alerts
|

Persian Adaptation of Foreign Language Reading Anxiety Scale: A Psychometric Analysis

Abstract: The validity and psychometric properties of a new Persian adaptation of the Foreign Language Reading Anxiety Scale were investigated. The scale was translated into Persian and administered to 160 undergraduate students (131 women, 29 men; M age = 23.4 yr., SD = 4.3). Rasch model analysis on the scale's original 20 items revealed that the data do not fit the partial credit model. Principal components analysis identified three factors: one related to feelings of anxiety about reading, the second reflected the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
(25 reference statements)
0
7
1
1
Order By: Relevance
“…Further exploration of category and threshold adjustment should be carefully considered, particularly for the passive function sub-scale, which had fewer items, rendering a low level of person reliability. While related studies have shown that a disordered threshold does not cause much problem for the model compared with some misfitting items [17,18], we found that rescoring seemed not to improve the fit to the model. Therefore, we preferred keeping the original 5-response options.…”
Section: Discussioncontrasting
confidence: 83%
“…Further exploration of category and threshold adjustment should be carefully considered, particularly for the passive function sub-scale, which had fewer items, rendering a low level of person reliability. While related studies have shown that a disordered threshold does not cause much problem for the model compared with some misfitting items [17,18], we found that rescoring seemed not to improve the fit to the model. Therefore, we preferred keeping the original 5-response options.…”
Section: Discussioncontrasting
confidence: 83%
“…Our result suggests that it is relevant to use another instrument to measure a more specific aspect of anxiety, in this case, anxiety in connection with the reading practice. As mentioned above, reading anxiety is a situation-specific anxiety experienced only in reading contexts (Baghaei et al, 2014;Piccolo et al, 2017;Zbornik, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess specific performance anxieties, instruments have been developed in different languages (Alkhateeb, 2014;Baghaei, Hohensinn, & Kubinger, 2014;Hsiao, 2002;Ramirez et al, 2019). Nonetheless, studies evaluating reading anxiety have been focused mostly on specific disorders in second language learners individuals (L2) (Chow, Chiu, & Wong, 2017;Guimba & Alico, 2016;Mohammadpur & Ghafournia, 2015;Zheng & Cheng, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yen (1993) lists a number of factors leading to local item dependence: test speededness, fatigue, practice, item or response format, passage dependence, and scoring rubrics or raters. These factors can affect test takers' performance on some test items that would likely load on second factors in a factor analysis (Yen, 1993;Baghaei, Hohensinn, & Kubinger, 2014).…”
mentioning
confidence: 99%